Mental disorders in preadolescent children at familial high‐risk of schizophrenia or bipolar disorder – a four‐year follow‐up study: The Danish High Risk and Resilience Study, VIA 11. (16th December 2021) - Gregersen, Maja; Søndergaard, Anne; Brandt, Julie Marie; Ellersgaard, Ditte; Rohd, Sinnika Birkehøj; Hjorthøj, Carsten; Ohland, Jessica; Krantz, Mette Falkenberg; Wilms, Martin; Andreassen, Anna Krogh; Knudsen, Christina Bruun; Veddum, Lotte; et al.
Abstract : Background: Children at familial high‐risk of schizophrenia and bipolar disorder have an elevated prevalence of mental disorders but studies of children within a narrow age range are lacking and there are few conjoint studies of these two groups. Knowledge on their mental health is important for prevention and early intervention. Methods: The authors examined mental disorders and global functioning in children at familial high‐risk of schizophrenia (FHR‐SZ) and bipolar disorder (FHR‐BP) compared with population‐based controls. In a longitudinal cohort study, 450 children (FHR‐SZ, n = 171; FHR‐BP, n = 104; controls, n = 175), were assessed for Axis I disorders at baseline and four‐year follow‐up (mean age 11.9, SD 0.2) with the Kiddie Schedule for Affective Disorders and Schizophrenia for School‐Age Children and for global functioning with Children's Global Assessment Scale. Results: Cumulative incidence of Any Axis I disorder was elevated by age 11 in children at FHR‐SZ (54.4%, OR 3.0, 95% CI 1.9–4.7, p < .001) and children at FHR‐BP (52.9%, OR 2.8, 95% CI 1.7–4.7, p < .001) compared with controls (28.6%). Children at FHR‐SZ and FHR‐BP had higher rates of affective disorders (OR 4.4, 95% CI 1.4–13.5, p = .009; OR 5.1, 95% CI 1.6–16.4, p = .007), anxiety disorders (OR 2.1, 95% CI 1.1–4.0, p = .02; OR 3.0, 95% CI 1.5–6.1, p = .002), and stress and adjustment disorders (OR 3.3, 95% CI 1.4–7.5, p = .006; OR 5.3, 95% CI 2.2–12.4, p < .001). Disruptive behavior disorders (OR 2.8, 95% CI 1.0–7.3, p = .04) and ADHD (OR 2.9, 95% CI 1.6–5.3, p < .001) were elevated in children at FHR‐SZ. Both FHR groups had lower global functioning than controls. Cumulative incidence of disorders increased equally across the three groups from early childhood to preadolescence and level of functioning did not change differentially. Conclusions: Children at FHR‐SZ and FHR‐BP have an elevated prevalence of mental disorders and poorer functioning than controls. Vulnerability in children at FHR manifests early and remains stable throughout childhood. Early attention toward their mental health and identification of those in need of intervention is warranted.